Apakah Transfer Tunai Pemerintah Memperburuk Modal Sosial? Kasus di Indonesia - Kharisma, Bayu (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.2, Agustus 2019 (pp. 111-247)DO - 10.24843/JEKT.2019.v12.i02.p03, 2019)
This paper aims to evaluate the impact of government policies in cash transfer on social capital in Indonesia. The method that will be used in this study are differences-in-differences (DID), while the data used is Indonesia Familiy Life Survey in 2000 and 2007. Based on the estimation results, the recipient of cash assistance is unconditional, namely cash assistance (BLT) more actively involved in social capital, especially in arisan activities. One of the household motivations to participate in arisan activities is to have access to credit and the ability to maintain purchasing power or carry out consumption smoothing when there is an increase in the price of fuel oil (BBM) in Indonesia. Meanwhile, the households that received unconditional cash assistance, namely the Program Keluarga Harapan did not have a statistical effect on social capital in Indonesia. These findings indicate that households that receive Program Keluarga Harapan assistance tend to be less active or involved in social capital activities in Indonesia.